4th Annual predictive toxicology summit 2012. (August 2013) - Cui, Zhanfeng
<x xml:space="preserve">Abstract</x> Introduction: This meeting report presents a brief summary on the 4th Annual Predictive Toxicology Summit 2012, which was held on 15 – 16 February 2012 in London. Areas covered: The majority of presentations came from global pharmaceutical companies, although small and medium enterprise (SME) and academic researchers were represented too. Major regulatory bodies were also present. The article highlights the summit, which was considered a good learning opportunity to catch up on the recent advances in predictive toxicology. Expert opinion: Predictive toxicology has become more and more important due to social and economic pressure and scientific reasons. Technological developments are rapid, but there is a gulf between the technology developers and the pharmaceutical end users; hence, early engagement is desirable. Stem cell-derived cell-based assays as well as three-dimensional in vitro tissue/organ model development are within the reach now, but a lot needs to be done to optimise and validate the developed protocols and products. The field of predictive toxicology needs fundamental research of interdisciplinary nature, which requires much needed trained personnel and funding.